Laparoscopy in endometrial cancer - Zevallos, Albert (2018)
Surgical staging is essential in the management of patients with endometrial cancer apparently confined to the uterus. Minimally invasive surgery (MIS) with its conventional laparoscopic approach or more recently with laparoscopic-assisted robotics has become the standard of management with advantage in terms of blood loss, hospital stay and quality of life compared to laparotomy. The pelvic and paraaortic lymphadenectomy as part of the surgical staging is determinant of the prognosis and sets the pattern of adjuvant treatment and although it is still controversial in terms of its therapeutic value, it is feasible through MIS. The performance of the sentinel lymph node with lower intraoperative complications and postoperative morbidity can be considered as an alternative to lymphadenectomy, especially considering the additional value of detecting low volume metastatic lymph node disease by means of immunohistochemistry.